2013
DOI: 10.1097/ede.0b013e3182a713a8
|View full text |Cite
|
Sign up to set email alerts
|

Do Interviewer and Physician Health Ratings Predict Mortality?

Abstract: Background Despite the serious biases that characterize self-rated health, researchers rely heavily on these ratings to predict mortality. Using newly collected survey data, we examine whether simple ratings of participants' health provided by interviewers and physicians can markedly improve mortality prediction. Methods We use data from a prospective cohort study based on a nationally representative sample of older adults in Taiwan. We estimate proportional hazard models of all-cause mortality between the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…Results from Taiwan suggest that the interviewer’s rating is a better mortality predictor than the rating of overall health provided by the respondent. Interviewers may base their evaluations not only on information directly obtained in the survey, but also on their observations of the respondent’s appearance, responsiveness, cognition, and disposition [ 18 ]. Although the physicians’ ratings are weak predictors, these physicians were seeing respondents for the first time and basing their judgments on only a routine physical examination and a medical history completed by the respondent.…”
Section: Discussionmentioning
confidence: 99%
“…Results from Taiwan suggest that the interviewer’s rating is a better mortality predictor than the rating of overall health provided by the respondent. Interviewers may base their evaluations not only on information directly obtained in the survey, but also on their observations of the respondent’s appearance, responsiveness, cognition, and disposition [ 18 ]. Although the physicians’ ratings are weak predictors, these physicians were seeing respondents for the first time and basing their judgments on only a routine physical examination and a medical history completed by the respondent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding on spouse's health report gained confirmation from some subsequent studies (Daugherty, 2009;Peek, Stimpson, Townsend et al, 2006). Meanwhile, a new line of research started to emerge with a focus on health evaluation by survey interviewers (Chen and Wu, 2008;Feng, Zhu, Zhen et al, 2016;Smith and Goldman, 2011;Todd and Goldman, 2013). According to these studies, the use of interviewer-rated health (IRH) may have some advantages over SRH in capturing health situations and may complement the routine use of SRH.…”
Section: Introductionmentioning
confidence: 75%
“…This is not a surprise. Compared to SRH, evaluation by interviewer could be less affected by subjective factors (Todd and Goldman, 2013) and thus may have some advantages over SRH (Brissette, Leventhal, and Leventhal, 2003). Because interviewers usually rate respondents' health at the end of the interview, which is the practice in the CLHLS, interviewers can incorporate information on a respondent's reported health and health-related conditions and information from their own observations while communicating with respondents.…”
Section: Discussionmentioning
confidence: 99%
“…It should perhaps be recalled here that the latter category included “poor” and “very poor”. Other studies have focused on the predictive ability of physician ratings: Giltay et al reported a better prognostic value for self-rated health than for physician-rated health when it came to predicting cancer mortality, while the opposite was true when it came to predicting cardiovascular deaths [ 5 ]; and a study on community-dwelling Taiwanese elders by Todd and Goldman yielded unexpected findings, in that physician ratings were observed to have a weak predictive power, and a clear, weaker predictive capacity as compared to both self-rated and interviewer-rated health [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…, while poor self-rated health was associated with cancer mortality, poor physician-rated health was associated with cardiovascular mortality [ 5 ]. In terms of mortality, Todd and Goldman reported that interviewer ratings displayed a better predictive behavior than did physician ratings in the case of older adults in Taiwan [ 6 ]. Physician-rated health has also been used in a number of studies as an adjustment variable, in an attempt to control for “objective” health status: for instance, Wilper et al observed a higher mortality risk associated with lack of health insurance, controlling for physician-rated health, among other variables [ 7 ]; and Moor et al used physician-rated health as an adjustment variable in a study on the association of neuroticism and subjective health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%